Upraszczanie wstępne reguł klasyfikacji drzew logicznych - Kubus, Mariusz (Pre-Pruning of Classification Rules for Logical Trees, 2007)
Discriminant models that ideally separate classes do not perform well on the new observations, especialy in the presence of noise. This is the general problem of discriminant analysis. Several technics of pruning were proposed in the literature to avoide overfitting. In this paper, pre-pruning technics that deal with noise during model generation are considered. The main goal of this paper is to adopt pre-pruning technics - used in classification trees and rules induction - for logical trees based discrimination method. The examples from UCI Repository of Machine Learning Databases are given.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 499-506